Pengaruh Kualitas Sumberdaya Manusia Terhadap Pembagunan Ekonomi Inklusif di Indonesia - Nurnaningsih, Nurnaningsih (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study examines the impact of poverty, unemployment, and economic inequality on inclusive growth in Indonesia. The data used in this study is panel data from 34 provinces in Indonesia. The analysis technique used is panel data regression with a fixed effect model. Based on the research results, it is clear that the relationship between poverty, unemployment, and economic inequality is negative and significant on inclusive economic growth in Indonesia. The analysis also emphasizes that efforts to achieve inclusive economic growth must focus on community empowerment, investment in education and training, inclusive infrastructure development, and policies focused on sustainable economic development